COMMISSIVE SPEECH ACTS IN THE COMMERCIAL ADVERTISEMENTS (TINDAK TUTUR KOMISIF DI DALAM IKLAN-IKLAN KOMERSIL) - Syafitri, Widdya; Sawirman, Sawirman; Usman, Fajri (Universitas PGRI Sumatera Barat, 2019)
Advertisement is a medium used to support an activity or a business. Through advertisement, the activity can spread out to the public or people. The study of advertisement can be associated to the field of pragmatics because it contains several speech acts used by the producer or the content creator to the target of the advertisements itself, which one of them is commissive speech act. In relation to its purpose that is to introduce or to promote a product, either things or services, the commissive speech act is an effective way to use to attract the public’s attention. This research is aimed at identifying and explaining the functions and the strategies of the commissive speech acts. The source of data is the commercial advertisements of household appliances and health products on MNC Shop in December 2018. The data are collected by using observational method with recording and writing technique and analyzed by using pragmatic identity method. The result of the research shows that the commissive speech acts in the commercial advertisements of MNC Shop comprise promising, giving a guarantee, making a bet, and convincing. Meanwhile, the strategies used are direct utterance, literal direct utterance, and literal indirect utterance.